Biologia populacional de Aegla sp. n.. (Crustacea, Decapoda, Aeglidae) no arroio Passo Taquara, São Pedro do Sul/RS - Trevisan, André (2008)
The aim of this study was to evaluate some aspects of the biology of the anomuran crab Aegla sp. n.., for example: the size of onset of sexual maturity, the median size between males and females, the sexual proportion (monthly and in size classes), the reproductive period (based on ovigerous females frequency), recruitment, spatial and seasonal distribution and growth in natural environment. This crustacean is a new species which is in process of description. The study was realized in Passo Taquara brook, situated in São Pedro do Sul municipality, in central region of Rio Grande do Sul State. Samplings were monthly realized, from May/2005 to April/2006 in three sections of the stream. Traps containing bovine liver as lure and dip nets were used to collect the animals. Eight traps were placed in each section, with a distance of 10 meters between them. In each section a sampling effort of 20 minutes was realized.. All the captured specimens were sexed by inspection of the presence of pleopods in females and and/or position of the sexual gonopores (coxae of the third pereopods in females and coxae of the fifth pereopods in males). Specimens with less than 3 mm of cephalothoracic length were considered unsexed juveniles due to the impossibility of visualizing pleopods and genital pores. The following corporeal dimensions were measured using a digital caliper with 0.01 mm of precision: cephalothoracic length (CL), cephalothoracic width (CW), width of the second abdominal somite (AW), length of the right chela (RC), length of the left chela (LC) and height of the larger chela (HC). After the data register, crabs were returned to the stream, to the same places where they were collected. A total of 916 specimens was sampled, 17 unsexed juveniles, 601 males (166 juveniles and 435 adults) and 298 females (101 juveniles, 182 adults and 25 ovigerous). The size at the onset of sexual maturity was esteemed, using Mature I and II software, in 13.60 and 10.84 mm of cephalothoracic length for males and females, respectively. Males presented sizes significantly larger than females. The distribution in size classes showed was bimodal for both sexes indicating more than one age-group in the population. The sexual proportion was in agreement with the expected value (1:1) when analyzing the specimens sampled with nets, but differed when analyzing the total data. Ovigerous females were sampled in all stations of the year, but they were more frequent in winter. Juveniles were also sampled in all stations of the years, but more frequently in winter and spring. The water temperature registered in Passo Taquara brook was similar among sections (p>0.05), but it was statistically more elevated in summer (p<0.05). The values of pH registered in section 02 were slightly more alkaline than in the other sections, and statistic differences among seasons were also observed (p<0.05). The concentrations of dissolved oxygen in water did not differ among sections, but the values observed in summer were significantly smaller (p<0.05). The outflow did not show statistic differences among sections and seasons (p>0.05). observed relationships in The linear regression analysis did not present any relationship between the abundance of eglids and the abiotic parameters, including precipitation (p>0.05). The type of substrate seems to be the principal factor explaining the distribution of this species, as revealed by the values of the linear regression between quantity of rocks and abundance of Aegla sp. n.. (F1,11 = 19.53 p = 0.0016). The size of rocks did not affect the abundance of eglids at the sections sampled. The growth curves of cephalothorax estimated for males and females are described by the following equations: Ct = 28.00 [1 e-0.0047(t+10.63)] and Ct = 25.16 [1 e-0.0051(t+17.65)], respectively. The males were larger than females and the estimated longevity was three years for males and two and half years for females. Differences were observed in the mean and median sizes of the chelipeds, besides a differential growth of the right and left chelae of Aegla sp. n.. The objective of this work was to contribute for the knowledge about some biology aspects of Aegla sp. n.., aiming the conservation of the species.